The Concentric Model of Russian Market for Economic Research - E. V. Balatsky; N. A. Ekimova (Мир новой экономики, 2018)
The article discusses the Rating of regional academic activity (Economics) for 2013-2015, which was built in the Financial University under the Government of the Russian Federation. Subject of research: Russian market of scientific research. Purpose of work: the study of spatial models of domestic scientific market. The results of the study allowed to conclude that the total concentration of the market scientific studies. An increasing number of regions excluded from the competitive process on the national market research. Almost all subjects of economic science are grouped in a limited spatial area, whereas other regions remain without prospects for further development. It discusses the possible implications of emerging trends and ways to overcome the problems identified.